New focuses on roles of communications between endoplasmic reticulum and mitochondria in identification of biomarkers and targets - Linlin Zhang (Wiley, 2021)
Abstract The communication between endoplasmic reticulum (ER) and mitochondria (Mt) plays important roles in maintenance of intra‐ and extra‐cellular microenvironment, metabolisms, signaling activities and cell‐cell communication. The present review aims to overview the advanced understanding about roles of ER‐Mt structural contacts, molecular interactions and chemical exchanges, signal transmissions and inter‐organelle regulations in ER‐Mt communication. We address how the ER‐Mt communication contributes to the regulation of lipid, amino acid and glucose metabolisms by enzymes, transporters and regulators in the process of biosynthesis. We specially emphasize the importance of deep understanding about molecular mechanisms of ER‐Mt communication for identification and development of biology‐specific, disease‐specific and metabolism‐specific biomarkers and therapeutic targets for human diseases. The inhibitors and modulators of the ER‐Mt communication are categorized according to therapeutic targets. Rapid development of biotechnologies will provide new insights for spatiotemporally understanding the molecular mechanisms of ER‐Mt communication.